Study the Influences of Electrolyte Solution on the Electrochemical and Magnetic Properties of LaNi4.6Ge0.4 Alloys - Dam, Nhan Ba (H. : ĐHQGHN, 2017)
In this report, we studied the effect of electrolyte concentration on the electrochemical and magnetic properties of the LaNi4.6Ge0.4 alloys used as the negative electrode in Ni-MH rechargeable batteries. Effect of electrolyte concentration on the electrochemical and magnetic properties of the LaNi4.6Ge0.4 alloys was investigated by the measurements of magnetization curves and charge-discharge performance of the material. The results showed that the composition electrolyte solution KOH(5.1) + LiOH(0.9), the charge-discharge performance is the highest. With this concentration of magnetization curves show superparamagnetic status and the magnetized values is the highest.